1998
DOI: 10.1016/s0741-5214(98)70088-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transrenal aortic endograft placement on endovascular graft repair of abdominal aortic aneurysms

Abstract: Transrenal aortic endograft fixation using a balloon expandable device in patients with AAAs can result in a significant reduction in the risk of proximal endoleaks. Absolute attention to precise device positioning, coupled with the use of detailed imaging techniques, should reduce the risk of inadvertent renal artery occlusion from malpositioning. Long-term follow-up is essential to determine if there will be late sequelae of transrenal fixation of endografts, which could adversely effect renal perfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(92 citation statements)
references
References 35 publications
(35 reference statements)
2
90
0
Order By: Relevance
“…3,5,6,16 Recent data confirm that even deploying solely suprarenal devices, intraoperative adjunctive interventions remain more frequent in severely angulated necks, 28 whereas other clinical studies have demonstrated that suprarenal aortic attachment is associated with reduced risk of proximal endoleaks. 29,32 Technical factors of the Endurant device, such as the wire-formed M-shaped bare laser-cut nitinol stents, the anchoring pins at proximal stent, and the controlled release of the top stent, are presumed to achieve accurate deployment and produce complete proximal sealing.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6,16 Recent data confirm that even deploying solely suprarenal devices, intraoperative adjunctive interventions remain more frequent in severely angulated necks, 28 whereas other clinical studies have demonstrated that suprarenal aortic attachment is associated with reduced risk of proximal endoleaks. 29,32 Technical factors of the Endurant device, such as the wire-formed M-shaped bare laser-cut nitinol stents, the anchoring pins at proximal stent, and the controlled release of the top stent, are presumed to achieve accurate deployment and produce complete proximal sealing.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several observational studies have reported the efficacy and safety of suprarenal endograft fixation. [280][281][282][283][284] Moreover, almost 50% and 87% of endografts used in the DREAM and EVAR-1 trials, respectively, were performed with endografts that used suprarenal fixation. Significantly, rates of renal dysfunction appear to be equivalent for endografts with transrenal nitinol or stainless steel stents and not significantly different among patients undergoing EVAR with infrarenal or suprarenal fixation.…”
Section: Endovascular Repairmentioning
confidence: 99%
“…In addition, a proximal uncovered portion allows for transrenal fixation, which may assist with the treatment of aneurysms with short aortic necks. 8,9 The Talent enhanced Low Profile System (eLPS; Medtronic Vascular, Santa Rosa, Calif), with the CoilTrac delivery system, received approval for use in EVAR from the United States Food and Drug Administration (FDA) in April 2008 based on data derived from the pivotal trial and the CoilTrac confirmatory study. The pivotal trial evaluated the safety and efficacy of the Talent eLPS compared with a historical open repair control group.…”
mentioning
confidence: 99%